Cycles of external dependency drive evolution of avian carotenoid networks - Alexander V. Badyaev (Nature Portfolio, 2019)
The mechanisms that accommodate variable external dependencies in evolution are not clear. Here, the authors show that switches between external and internal metabolic controls of carotenoid-producing networks in birds are linked to shifts in evolutionary rates, with internalization of control resulting in bursts of evolutionary diversification.